Dimension-specific symptom patterns in trajectories of broad anxiety: A longitudinal prospective study in school-aged children. (February 2020) - Ahlen, Johan; Ghaderi, Ata
Abstract: Theories of maladaptive anxiety in children have suggested different developmental trajectories across age. Weems (2008) suggested that one subgroup of children demonstrates high and stable levels of broad anxiety, but shifting levels of dimension-specific symptoms in part due to related normative challenges. In a prospective longitudinal design, the current study examined patterns of dimension-specific anxiety symptoms in subgroups of children following different developmental trajectories of broad anxiety. A total of 300 children (150 girls, 150 boys) ages 8–11 at baseline, completed the Spence Children's Anxiety Scale four times over 3 years. Using latent class growth mixture modeling, we found evidence of three subgroups of children following different trajectories of broad anxiety across age: low-stable, moderate-increasing, and high-decreasing. Compared with other children, the subgroup with moderate and increasing levels of broad anxiety demonstrated an initially higher level of separation anxiety with larger improvement across time but, initially, similar levels of generalized and social anxiety with a larger increase across age. High broad anxiety was partly carried by different sets of dimension-specific symptoms at different ages, which suggests that children with high levels of broad anxiety across time may be more sensitive to normative challenges that happen in typical child development.